Deoxynivalenol biosynthesis and accumulation in wheat under application of carrageenan - Ducatti, Rafael Dal Bosco; Wordell Filho, João Americo; Mazaro, Sergio Miguel (Revista de Ciências Agroveterinárias, 2022)
Mycotoxins pose a large threat to human and livestock besides reducing the quality of food/feed. It is believed that these toxins are biosynthesized as a mechanism of defense (stress-response) of fungi. The most important mycotoxin for winter-cereal crops is known by deoxynivalenol (DON), a trichothecene biosynthesized mainly by Fusarium graminearum. This manuscript brings data of three years (2018, 2019 and 2020) of field research (24 field experiments) in Western Santa Catarina and North-Western Rio Grande do Sul, Brazil using a sulphated polysaccharide exclusive from red seaweed, carrageenan, associated with fungicides to help suppressing deoxynivalenol (DON) biosynthesis and accumulation in wheat kernels. A reduction of 36.4% in DON contamination was observed. Weather conditions have influenced the accumulation of DON in wheat kernels. Carrageenan has shown to be a biological compound capable of helping on the suppression of DON biosynthesis and accumulation in wheat kernels regardless of weather conditions.